2021
DOI: 10.1108/ijrdm-09-2020-0356
|View full text |Cite
|
Sign up to set email alerts
|

The role of social embarrassment, sustainability, familiarity and perception of hygiene in second-hand clothing purchase experience

Abstract: PurposeSecond-hand clothing (SHC) has kindled a growing interest among researchers and practitioners. However, despite all the benefits that this market presents, consumer adherence still has considerable room for improvement. Several studies have explored the main motivations that lead consumers to buy second-hand clothes (SHCs), but few have focused on the factors that prevent consumers from adopting this consumption behavior. Hence, this study aims to identify barriers through the differences in the percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 54 publications
4
48
2
1
Order By: Relevance
“…Intention to buy secondhand clothing consumers evaluate how their significant ones think about the behaviour and observe whether their significant ones engage in that behaviour. Several studies reported that people avoid buying second-hand clothing because of social embarrassment (Sandes and Leandro, 2016;Silva et al, 2021;Laitala and Klepp, 2018) as second-hand clothing is typically associated with low-income groups. Surprisingly, our finding does not corroborate the finding of Seo and Kim (2019) that injunctive norms do not affect consumers' intention to buy second-hand clothing in non-profit thrift stores.…”
Section: Structural Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intention to buy secondhand clothing consumers evaluate how their significant ones think about the behaviour and observe whether their significant ones engage in that behaviour. Several studies reported that people avoid buying second-hand clothing because of social embarrassment (Sandes and Leandro, 2016;Silva et al, 2021;Laitala and Klepp, 2018) as second-hand clothing is typically associated with low-income groups. Surprisingly, our finding does not corroborate the finding of Seo and Kim (2019) that injunctive norms do not affect consumers' intention to buy second-hand clothing in non-profit thrift stores.…”
Section: Structural Model Resultsmentioning
confidence: 99%
“…Consumers are becoming more eco-conscious and more willing to adopt responsible consumption by giving products a second life (Silva et al, 2021). People who have high levels of environmental value are more likely to engage in behaviours that are beneficial to the environment.…”
Section: Environmental Valuementioning
confidence: 99%
“…Silva et al [24] identify three types of barriers to consumer engagement in SHF: functional, psychological and social. In our literature review, we focus on functional barriers, which are defined as those arising from functional or utilitarian purposes.…”
Section: Analysis Of Barriers To Consumer Engagementmentioning
confidence: 99%
“…The focus is on barriers to buying SHF instore and that remains relevant in a digital environment. This also means that only 'functional barriers,' defined as those arising from their functional or utilitarian purposes, were included in the analysis and not 'psychological barriers' [24].…”
Section: Analysis Of Barriers To Consumer Engagementmentioning
confidence: 99%
“…These questions are important because to date, there is little information regarding the effect of sustainable attributes in clothing selection on the frequency of sustainable purchase and post-purchase actions among different segments of the population. Most of the research published to date that has attempted to recognise determinants of sustainable purchase and post-purchase behaviour has analysed personal demographic or psychological characteristics [ 17 , 18 ], the influence of the social environment [ 19 , 20 ] and the impact of cultural conditions [ 21 , 22 ] on behaviours such as the purchase of second-hand clothing or post-purchase behaviours such as fashion clothing disposal behaviour.…”
Section: Introductionmentioning
confidence: 99%